COMPUTATIONAL OFFLOADING FOR PERFORMANCE IMPROVEMENT AND ENERGY SAVING IN MOBILE DEVICES - Chen, Joy Iong Zong (IRO Journal on Sustainable Wireless Systems, 2019)
The mobiles devices such as the smart phones and the wearables take a vital role in our daily life scenario as they are been used as alternative for many devices apart from communication. The mobile devices that are controlled in terms of dimensions and weightiness to make them easy and flexible for handling in turn limits the computational energy, storage and the lifetime of the battery. So this entails the need for the external device to support the mobile devices by providing a computational power, storage and energy, this is known as the computational offloading. So the paper puts forth the mobile cloud services as an external platform to offload the resource intensive computation tasks of the mobile devices to enhance the performance of the mobile devices in terms of storage, energy consumption and battery life. The performance evaluation of the mobile cloud based offloading in the mobile devices proves the efficiency of the proffered method in terms of storage, energy and battery lifetime.